FEATURES OF DOMESTIC REGULATORY FRAMEWORK GOVERNING CATHODIC PROTECTION OF HEATING NETWORKS AGAINST EXTERNAL CORROSION IN THE GROUND - V. G. Kiselev; E. N. Ruzich (Известия высших учебных заведений: Проблемы энергетики, 2019)
Abstract: Paper provides comparative analysis of basic regulations governing design of systems of cathodic protection of underground metal structures against corrosion based on both Russian and international materials. The following basic parameters for evaluation of cathodic protection system performance are accepted: "need for applying cathodic protection systems", "values characterizing security of underground metal structures against corrosion in the presence of electrochemical protection", "density of protective current" and "magnitude of protective current". Carried out analysis identified the need to improve Russian system of cathodic protection systems design for all listed characteristics and above all in the direction of reducing the quantities of protective current and its density.